2020
DOI: 10.1088/1741-2552/ab5eda
|View full text |Cite
|
Sign up to set email alerts
|

Impact of parameter selection on estimates of motoneuron excitability using paired motor unit analysis

Abstract: Objective.-Noninvasive estimation of motoneuron excitability in human motoneurons is achieved through a paired motor unit analysis (ΔF) that quantifies hysteresis in the instantaneous firing rates at motor unit recruitment and de-recruitment. The ΔF technique provides insight into the magnitude of neuromodulatory synaptic input and persistent inward currents (PICs). While the ΔF technique is commonly used for estimating motoneuron excitability during voluntary contractions, computational parameters used for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 37 publications
2
69
0
Order By: Relevance
“…Second, Kim et al, 24 and Afsharipour et al, 23 did not track the same motor units across contractions intensities. As previously reported 27 , there is a large between-motor unit variability in ΔFs, which might have reduced the sensitivity of the variable to detect differences among contractions intensities. Third, both studies compared ΔFs obtained from different populations of motor units.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Second, Kim et al, 24 and Afsharipour et al, 23 did not track the same motor units across contractions intensities. As previously reported 27 , there is a large between-motor unit variability in ΔFs, which might have reduced the sensitivity of the variable to detect differences among contractions intensities. Third, both studies compared ΔFs obtained from different populations of motor units.…”
Section: Discussionmentioning
confidence: 83%
“…Next, participants were familiarised with both trapezoidal and triangular ramped contractions. Both triangular and trapezoidal contractions have been used previously to calculate ΔFs using the paired motor unit analysis 26,27 . These ramp-shaped contractions were performed to 10, 20 and 30% of their maximal voluntary contraction torque.…”
Section: Study Design and Neuromuscular Testing Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulations showed that a decoder that captures the initial firing rate as well as estimates the relative change in firing gain between the secondary and tertiary spiking phases could decode the excitation level to MNs accurately. Importantly, these parameters could be easily and accurately estimated from pool or cellular spiking in humans (Farina et al, 2017;Afsharipour et al, 2020;Hassan et al, 2020). While decoding MN spiking activity for estimating the synaptic input (as a measure of motor intent) or for estimating grip force have been recently examined in animals (Thompson et al, 2018) and humans (Farina et al, 2017;Twardowski et al, 2019;Afsharipour et al, 2020;Hassan et al, 2020), only one decoder in the literature has shown real-time performance for prosthetic control (decoding time < 10 ms, Twardowski et al, 2019).…”
Section: Current Work Vs Earlier Mn Decodersmentioning
confidence: 99%
“…Importantly, these parameters could be easily and accurately estimated from pool or cellular spiking in humans (Farina et al, 2017;Afsharipour et al, 2020;Hassan et al, 2020). While decoding MN spiking activity for estimating the synaptic input (as a measure of motor intent) or for estimating grip force have been recently examined in animals (Thompson et al, 2018) and humans (Farina et al, 2017;Twardowski et al, 2019;Afsharipour et al, 2020;Hassan et al, 2020), only one decoder in the literature has shown real-time performance for prosthetic control (decoding time < 10 ms, Twardowski et al, 2019). When compared to conventional amplitudebased myoelectric decoders, MN firing activity-based decoders provide more responsive, smooth, and proportional control, supporting the high performance in Twardowski et al (2019) and even higher performance observed in our results (see Pearson's CC, RMSE, and NRMSE, next section).…”
Section: Current Work Vs Earlier Mn Decodersmentioning
confidence: 99%